Degradation of ferritic stainless steels under conditions used for solid oxide fuel cells and electrolyzers at varying oxygen pressures. (September 2016) - Alnegren, P.; Sattari, M.; Froitzheim, J.; Svensson, J-E.
Highlights: High temperature oxidation of a few ferritic steels was investigated as a function of oxygen pressure. The oxidation rate did not vary significantly with oxygen pressure in the test atmosphere. The formed oxide scales contained smaller grains in lower oxygen pressure. Abstract: Four commercial ferritic stainless steels were tested at 850 °C in oxygen pressures ranging from 10 −4 to 1 atm, in order to investigate the isolated effect of oxygen pressure on corrosion, in the context of solid oxide electrolysis cells. The oxidation rates of all steels were essentially independent of oxygen partial pressure, which indicates n-type behavior. FIB/SEM analysis revealed that the grain size of the oxides was found to decrease at lower oxygen pressures. Volatile Cr species evaporation in pure oxygen was significantly lower than what has been reported for simulated solid oxide fuel cell environments with humid air.